If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9s + -44 = 2s + 5 Reorder the terms: -44 + 9s = 2s + 5 Reorder the terms: -44 + 9s = 5 + 2s Solving -44 + 9s = 5 + 2s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-2s' to each side of the equation. -44 + 9s + -2s = 5 + 2s + -2s Combine like terms: 9s + -2s = 7s -44 + 7s = 5 + 2s + -2s Combine like terms: 2s + -2s = 0 -44 + 7s = 5 + 0 -44 + 7s = 5 Add '44' to each side of the equation. -44 + 44 + 7s = 5 + 44 Combine like terms: -44 + 44 = 0 0 + 7s = 5 + 44 7s = 5 + 44 Combine like terms: 5 + 44 = 49 7s = 49 Divide each side by '7'. s = 7 Simplifying s = 7
| 48+8y=16y+16 | | 9x+6(100)=7x+700 | | (q+33)+6q=180 | | M+-5=-10 | | z+12=5z | | 92=x(x+4) | | a^4b^6/ab^3 | | 5/8x-51/8x=3/2 | | 9x+6(100)= | | 3q-r=7 | | 483575.32=19105.8019x^(5/2)-60446.915x | | 2=9y/4 | | 18=(4/3x)(-3/2x) | | 5/4=z/8 | | 8+6(x-3)=2-7(x-6) | | 4x*2x^2=0 | | 5/4=2/8 | | 20x-(2x-4)=40 | | (4x+7)+(2x-1)=180 | | K-7=-9 | | 3(1-2x)=2(5x-1) | | 5x+20=4x+20 | | 14+6=-4(4x-5) | | 4x-12-3x+9=2x+8 | | 2x(x-6)(3x+2)=0 | | 5a^2+3a-2=0 | | -2.3-3x-4.1-x=-3x-0.9 | | ln(3x-6)=8 | | K+12=10 | | K+10=10 | | 3x-2x+8=5x+5+3 | | -2+n=6n+22 |